ZONING OF MODERN LANDSCAPES OF TALYSH MOUNTAINS FOR RECREATIONAL AND TOURIST POTENTIAL - GULIYEVA, Ilaha (Ekonomichna ta Sotsialna Geografiya, 2017)
Recreational zoning of landscapes constitutes of the fundamental geographical concepts. Based on the literature we concluded that there is no consensus among researchers regarding the methodology and principles of recreational zoning. Our proposed zoning of the Talysh Mountains region is based on the estimation of the recreational resources of modern landscapes. The recreational resource of the territory is determined on the basis of the following indicators: relief, climatic conditions, vegetation (especially forest one), water objects, aesthetic attractiveness and diversity of the landscape, quality of infrastructure, etc. Recreational resources of individual regions within the investigated territory were determined taking into account their natural landscapes, level of development, significance of certain resources, their structure, etc. Based on these criteria, five recreation areas were identified in Talysh region and corresponding maps have been drawn up.

Рекреаційне районування ландшафтів є одним з основних фундаментальних понять географії. В результаті аналізу різних літературних джерел можна прийти до висновку про відсутність єдиної думки дослідників щодо методики та принципів рекреаційного районування. Наша спроба рекреаційного районування території Талиських гір ґрунтується на оцінці рекреаційних ресурсів їх сучасних ландшафтів. Рекреаційний ресурс території визначається на основі наведених нижче показників: рельєф, кліматичні умови, рослинний покрив (особливо лісовий), водні об’єкти, естетична привабливість і різноманітність ландшафту, якість інфраструктури тощо. В результаті проведеного дослідження визначено рекреаційні ресурси окремих регіонів досліджуваної території, враховуючи наявні природні ландшафти, ступінь освоєння територій, значущість окремих видів ресурсів, їх структуру тощо. На основі цих принципів в межах регіону Талиських гір виділено 5 рекреаційних районів та укладено відповідні карти.
РАЙОНУВАННЯ СУЧАСНИХ ЛАНДШАФТІВ ТАЛИСЬКИХ ГІР ЗА РЕКРЕАЦІЙНО-ТУРИСТИЧНИМ ПОТЕНЦІАЛОМ
Keywords: recreational resources; recreational zoning; recreational potential; landscape; estimation of recreational potential; рекреаційні ресурси; рекреаційне районування; рекреаційний потенціал; ландшафт; оцінка рекреаційного потенціалу